Molecular genetic variation in a widespread forest tree species Eucalyptus obliqua (Myrtaceae) on the island of Tasmania - Bloomfield, J.; Nevill, Paul; Potts, B.; Vaillancourt, R.; Steane, D. (CSIRO Publishing, 2011)
Eucalyptus obliqua L'H´r. is widespread across south-eastern Australia. On the island of Tasmania it has a more-or-less continuous distribution across its range and it dominates much of the wet sclerophyll forest managed for forestry purposes. To understand better the distribution of genetic variation in these native forests we examined nuclear microsatellite diversity in 432 mature individuals from 20 populations of E. obliqua across Tasmania, including populations from each end of three locally steep environmental gradients. In addition, chloroplast microsatellite loci were assessed in 297 individuals across 31 populations. Nuclear microsatellite diversity values in E. obliqua were high (average HE=0.80) and inbreeding coefficients low (average F=0.02) within these populations. The degree of differentiation between populations was very low (F ST=0.015). No significant microsatellite differentiation could be found across three locally steep environmental gradients, even though there is significant genetic differentiation in quantitative traits. This suggests that the observed quantitative variation is maintained by natural selection. Population differentiation based on chloroplast haplotypes was high (G ST=0.69) compared with that based on nuclear microsatellites, suggesting that pollen-mediated gene flow is 150 times the level of seed-mediated gene flow in this animal-pollinated species; hence, pollen is likely to be the main mode of gene flow countering selection along local environmental gradients. Implications of these results for silvicultural practices are discussed. © 2011 CSIRO.